Magnetoelastic effects in low-dimensional magnetic systems - Zvyagin, A. A.; Zvyagina, G. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
We consider a new realization of magnetoelastic interactions in low-dimensional magnetic systems.We show that low-dimensional spin systems are unstable with respect to the spontaneous appearance ofalternating distortions of the positions of the three-dimensional nonmagnetic atoms (ligands), that surround the magnetic ions. Those distortions are supplemented by the spontaneous onset of alternatingeffective g factors of the magnetic ions in the phase with short-range interactions. We discuss the possibility of observing the effect in an uniform external magnetic field, which in the situation considered produces both magnetization and staggered magnetization of the magnetic subsystem. The connection of the proposed theory with recent experiments on effectively low-dimensional magnetic systems (organic spin chains, heavy-fermion compounds, rare-earth molybdates) is discussed.